4-Miktoarm star architecture induces PVDF β-phase formation in (PVDF)2-b-(PEO)2 miktoarm star copolymers. Issue 39 (28th September 2020) - María, Nicolás; Maiz, Jon; Rodionov, Valentin; Hadjichristidis, Nikos; Müller, Alejandro J.
Abstract : PVDF based newly synthesized 4-miktoarm star copolymers exhibit remarkable crystallization properties and polymorphism. Abstract : Novel (PVDF)2 - b -(PEO)2 4-miktoarm star copolymers (PVDF: polyvinylidene fluoride, PEO: polyethylene oxide) with three different compositions, but the same overall molecular weight, were synthesized by combining iodine transfer and anionic polymerizations with "click" chemistry. We have studied the polymorphic character of the PVDF arm crystals in the 4-miktoarm star copolymers in comparison with one of their 2-arm star (linear) precursors ((PVDF29 -N3 )2 ), when the samples are cooled from the melt at different cooling rates. The phase behaviour was investigated by small angle X-ray scattering (SAXS) and polarized light optical microscopy (PLOM). The results indicate that the materials are either weakly segregated in the melt or melt-mixed. They form PVDF spherulites at high crystallization temperatures when the PEO component is molten. The relative contributions of the α and β-phase were determined by in situ wide angle X-ray scattering (WAXS), differential scanning calorimetry (DSC) and Fourier transform infrared spectroscopy. All samples exhibit a mixture of α and β-phase crystals when cooled from the melt at 20 °C min −1 . However, the amount of β-phase is much larger in the 4-miktoarm star copolymer samples than in the (PVDF29 -N3 )2 linear precursor. Therefore, the 4-miktoarm star chain topology was found to induce β-phase formation. As the samples are cooled at slower rates, the amount of PVDF β-phase crystals increased. For samples crystallized at 1 °C min −1, the PVDF arms of all the synthesized (PVDF)2 - b -(PEO)2 miktoarm star copolymers form exclusively the ferroelectric/piezoelectric β-phase crystals. Therefore, these materials have potential applications in the field of energy harvesting.